2019
DOI: 10.1002/hep.30625
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between PNPLA3 rs738409 Polymorphism and Decreased Kidney Function in Children With NAFLD

Abstract: Emerging evidence suggests that patatin‐like phospholipase domain–containing protein‐3 (PNPLA3) rs738409 genotype (the major genetic variant associated with susceptibility to nonalcoholic fatty liver disease [NAFLD]) is associated with decreased kidney function in adults. Currently, it is uncertain whether this association also occurs in children/adolescents and whether any association is independent of liver disease severity. We enrolled a sample of 142 Caucasian children and adolescents with biopsy‐proven NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 29 publications
(51 reference statements)
7
49
1
1
Order By: Relevance
“…Moreover, recently, Targher et al showed that—in children with histologically confirmed NAFLD—the patients homozygous for the PNPLA3 rare allele had lower eGFR and higher 24‐hour proteinuria compared with other genotypes …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recently, Targher et al showed that—in children with histologically confirmed NAFLD—the patients homozygous for the PNPLA3 rare allele had lower eGFR and higher 24‐hour proteinuria compared with other genotypes …”
Section: Discussionmentioning
confidence: 99%
“…These findings were also replicated in some cohorts of children and adolescents [28,29], although not in all [30]. For instance, in a sample of nearly 140 overweight children with NAFLD on histology, Targher et al [28], reported that rs738409 G/G genotype was independently associated with both decreasing e-GFR and increasing 24 h urinary protein excretion. Another cross-sectional study involving 591 Caucasian children with obesity, it was documented that those with G/G genotype had significantly lower eGFR levels than those with G/C or C/C genotypes [29].…”
Section: Observational Data Regarding the Role Of Pnpla3 On The Risk mentioning
confidence: 86%
“…Increasing evidence now supports the existence of an association between PNPLA3 G/G genotype and decreasing eGFR values or higher prevalence of CKD across different patient population, even after controlling for many CKD risk factors and for the presence of NAFLD [24][25][26][27][28][29][30] (Table 1). For instance, in a cross-sectional study of 740 Japanese individuals (about 16% of whom had NAFLD on ultrasonography), Oniki et al [24], showed that patients with rs738409 G/G genotype had lower eGFR values than those with G/C or C/C genotypes, even after adjustment for multiple cardio-renal and metabolic risk factors.…”
Section: Observational Data Regarding the Role Of Pnpla3 On The Risk mentioning
confidence: 99%
See 2 more Smart Citations